Recent research advances in meat analogues: a comprehensive review on production, protein sources, quality attributes, analytical techniques used, and consumer perception - Baig, Mohammad Affan; Ajayi, Feyisola Fisayo; Hamdi, Marwa; Baba, Waqas; Brishti, Fatema Hossain; Khalid, Nauman; Zhou, Weibaio; Maqsood, Sajid (Taylor and Francis, 2025)
Recently, there has been significant research on plant-based meat as a substitute for animal meat. However, developing meat analogues with suitable techno-functional properties and a meat-like texture presents several challenges. In lieu of animal meat, plant-based meats offer a sustainable and healthy alternative. The nutritional and textural properties of meat analogues are mostly influenced by the specific type of proteins utilized and the various processing techniques implemented. Despite this, alternative proteins sourced from various plants such as legumes, pulses, and cereals, continue to be underutilized, with limited research done on their use in meat analogue development. The sustainability of production technologies and the selection of proteins can have a direct impact on both cost effectiveness and consumer of meat analogues. The challenges associated with the development of gluten-free meat analogues are currently being examined. Moreover, the extraction techniques employed in the isolation of plant proteins are of paramount importance, as they contribute to the organoleptic and textural attributes of meat analogues. By utilizing advanced technologies to sustainably utilize diverse plant proteins, it is feasible to conquer the challenges encountered in the production of plant-based meat products that are palatable to both consumers and the food industry. In this review we have discussed the functional roles of various ingredients and additives for enhancing nutritional and textural properties of meat analogues and current technologies used for texturizing plant-based meat analogues. Further we have discussed various analytical methods for testing the quality attributes of meat analogues and technological and consumer perception/acceptability-related challenges and opportunities.